The Miocene/Pliocene Boundary In The North East Java Basin, Indonesia - Soemoenar Soeka; Suminta Suminta; Siswoyo Siswoyo (Testing Center for Oil and Gas LEMIGAS, 1982)
As a part of the LEMIGAS Research Programme on Neogene Epoch Boundaries in the Indonesian Tertiary Basins, in 1981 fiscal year is selected North East Java Basin as an object for research. In this paper we will stress our work on the Miocene/ Pliocene Boundary of the basin based on planktonic Foraminifera. More recently a lot of paleontologists have been working on the Miocene/Pliocene Boundary problem. Bandy (1963) used the first appearance of Sphaeroidinella dihescens as a boundary in the Phillipine, whereas boundary based on the initial apppearance of Globoratalia margaritae. carried out an examination of samples from the Trubi Marl of the Zanclean Sicily and came to the conclusion approximately with middle N18 of this zonal scheme. Bolli ( 1966, revision in 19/0 ) put this stage In 1969, Blow Berggren (1973) proposed the limit of this stage boundary based on the last occurrence of Globoquadrina dehiscens. Kaneps (1974) based on this observation on planktonic Foraminifera of the DSDP cores from the Eastern Equatorial Pacific Ocean came to the conclusion that the Miocene/Pliocene Boundary lies at the base of Globoratalia tumida zone. The base of this zone was placed at the horizon of the initial appearance of Globoratalia tumida while the upper boundary was placed at the horizon of reversal in coiling direction of Pulleniatina primalis from left below to right above. Pringgoprawiro and Baharuddin (1979) on the other hand proposed the initial appearance of Sphaeroidinella immatura as a boundary between these two periods. The purpose of this paper is to study the ranges of some selected important species, and to detect how far these species can be used as a tool for Miocene/Pliocene Boundary in the North East Java Basin. No radiometric age dating has been done in the area.